Comparison Between High- and Low-Intensity Static Stretching Training Program on Active and Passive Properties of Plantar Flexors - Nakamura, Masatoshi; Yoshida, Riku; Sato, Shigeru; Yahata, Kaoru; Murakami, Yuta; Kasahara, Kazuki; Fukaya, Taizan; Takeuchi, Kosuke; Nunes, João Pedro; Konrad, Andreas (Frontiers in Physiology, 2021)
The purpose of this study was to compare two static stretching (SS) programs at high-intensity (HI-SS) and normal-intensity (NI-SS) on passive and active properties of the plantar flexor muscles. Forty healthy young men were randomly allocated into three groups: HI-SS intervention group (n=14), NI-SS intervention group (n=13), and non-training control group (n=13). An 11-point numerical scale (0-10; none to very painful stretching) was used to determine SS intensity. HI-SS and NI-SS trained at 6-7 and 0-1 intensities, respectively, both in 3 sets of 60 secs, 3x/week, for 4 weeks. Dorsiflexion range of motion (ROM), gastrocnemius muscle stiffness, muscle strength, drop jump height, and muscle architecture were assessed before and after training. The HI-SS group improved more than NI-SS in ROM (40% vs. 15%) and muscle stiffness (-57% vs. -24%), while no significant change was observed for muscle strength, drop jump height, and muscle architecture in both groups. The control group presented no significant change in any variable. Performing HI-SS is more effective than NI-SS for increasing ROM and decreasing muscle stiffness of plantar flexor muscles following a 4-week training period in young men. However, SS may not increase muscle strength or hypertrophy, regardless of the stretching discomfort intensity.